Impression Cytology Is a Non-invasive and Effective Method for Ocular Cell Retrieval of Zika Infected Babies: Perspectives in OMIC Studies - Barbosa, Raquel Hora; dos Santos, Maria Luiza B.; Silva, Thiago P.; Rosa-Fernandes, Liva; Pinto, Ana M. V.; Spínola, Pricila S.; Bonvicino, Cibele R.; Fernandes, Priscila V.; Lucena, Evandro; Palmisano, Giuseppe; Melo, Rossana C. N.; Cardoso, Claudete Aparecida Araújo; et al. (Frontiers in Molecular Neuroscience, 2019)
Non-invasive techniques for retrieving ocular surface cells from babies infected by zika virus (ZIKV) during the gestational period remain to be determined. The aim of this study was to describe an optimized impression cytology method for the isolation of viable cells from Zika infected babies with and without Congenital Zika Syndrome (CZS) in satisfactory amounts and quality to enable easy adoption in the field and application in the context of genomic and molecular approaches. Ocular surface samples were obtained with a hydrophilic nitrocellulose membrane (through optimized impression cytology method) from twelve babies referred to the Pediatric Service of the Antonio Pedro Hospital, Universidade Federal Fluminense (UFF), Rio de Janeiro, Brazil. After an authorized written informed consent from the parents, samples were collected from both eyes of 12 babies (4 babies with maternal ZIKV exposure during gestation and presence of clinical signs which included ocular abnormalities and microcephaly; 4 babies with maternal ZIKV exposure during gestation but no clinical signs; and 4 unaffected control babies with negative PCR for Zika virus and without clinical signs). Cells were used for microscopy analyses and evaluated for their suitability for downstream molecular applications in transcriptomic and proteomic experiments. Our optimized impression cytology protocol enabled the capture of a considerable number of viable cells. The microscopic features of the conjunctival epithelial cells were described by both direct analysis of the membrane-attached cells and analysis of cytospinned captured cells using several staining procedures. Epithelial basal, polyhedral and goblet cells were clearly identified in all groups. All cases of ZIKV infected babies showed potential morphological alterations (cell keratinization, pyknosis, karyolysis, anucleation and vacuolization). Molecular approaches were also performed in parallel. Genomic DNA and RNA were successfully isolated from all samples to enable the establishment of transcriptomic and proteomic studies. Our method proved to be a suitable, fast, and non-invasive tool to obtain ocular cell preparations from babies with and without Zika infection. The method yielded sufficient cells for detailed morphological and molecular analyses of samples. We discuss perspectives for the application of impression cytology in the context of ZIKV studies with OMIC in basic and clinical research.